Cultivated terraces in Slovenian landscapes - Šmid Hribar, Mateja; Geršič, Matjaž; Pipan, Primož; Repolusk, Peter; Tiran, Jernej; Topole, Maja; Ciglič, Rok (Acta geographica Slovenica, 2017)
Cultivated terraces distinctively mark the landscape and are a result of human adaptation to steep areas. Terraces were studied with regard to their morphometric qualities, ownership structure, and land use at eight pilot sites in various landscape types in Slovenia. Twenty-six detailed interviews were carried out with local residents and experts. In current agricultural practice, terraces mostly represent obstacles, and for owners they create a loss rather than profit; however, they represented an advantage in the past, when they were cultivated manually. Land use is intensifying on economically profitable terraces. Among those examined, the Jeruzalem terraces stand out because these are the youngest ones (created in socialist Yugoslavia around 1965). Because of their aesthetic value, they are the best known among the public. Profitability in particular will be an important driving force for the future maintenance of terraces.